An Analysis of Objective Reality towards Surgical Nursing Public Service Management at the Makassar Regional Hospital - Harniati Harniati; Arjang Arjang; Abd. Rahman; Fadlyah Fadlyah; Sudiarti Dewi Kurra (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The aim of this research was to describe, interpret, and analyze an objective reality of surgical nursing service management at Makassar Regional Hospital. A qualitative approach has been employed since the data were gathered through interviews, observation, and documentation. Some significant findings to emerge from this research are the general performance of surgical nursing service management at the Makassar Regional Hospital which have utilized management resources as inputs. Those are also determinably managed through proper managerial processes with some outputs referring to the hospital service standard indicator. The process of supervision in the context of surgical nursing service management automatically runs by forcing the implementation of valid Standard Operating Procedure in surgery. In line with that, the management evaluation have been done periodically but not in the context of core business process analysis. As a result, it is recommended for three features of the business process analysis to be further added: the first is by measuring the performance quality towards customers’ (patients) attributes for improving service accuracy and precision; the second is by updating the system to increase the process effectiveness of nursing service management through identified evaluation; and the last is by optimizing an efficient productivity.